Characterization of Plasma Cured E-Glass-Epoxy composite. (2020) - Beura, S.; Chakraverty, A.P.; Sarangi, Swetalin; Mohanty, U.K.; Thatoi, D.N.
Abstract: Glass fiber (E-Glass) reinforced polymer Epoxy-resign, composite seats were fabricated in the laboratory by hand-lay-up method with 6, 12 and 18 layers of laminates. Short-beam-shear (SBS) specimens were machined out of the fabricated seats. The 6 layer SBS specimens were exposed to low temperature plasma for 5, 10, 15 and 20munits. The specimens developed the maximum ILSS (Inter Laminar Shear Stress), for the 6 layered samples with 15 minute of exposure to the low temperature plasma due to post-cure strengthening. on the basis of the above, 12 and 18 layered SBS specimens were also exposed to the same low temperature plasma for 15 minutes duration. The observed ILSS values for the 12 layered specimens were somewhat higher than the same for the 18 layered specimens while being less than the 6 layered once. The least ILSS values were recorded for the 18 play samples. Thus, the radial migration of low temperature plasma inside the core of the specimens, responsible for post cure strengthening was inferred to bea function of the no of layers in the composite specimens, decreasing with the increase in the no of layers responsible for an increase in the thickness of the specimens. Glass transition temperature (Tg ) for these plasma cured samples with 15 minute exposure (optimum) also decreased with the increase in the no of layers in the specimens. The mode of failure, as reviled from SEM fractographs, included fiber-pull-out, fiber-matrix debonding, matrix cracking/ crazing and fiber breaking